PENGEMBANGAN BUKU SAKU DIGITAL BISA.ID SEBAGAI MEDIA LITERASI PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Irma, Cintya Nurika; Wakhyudi, Yukhsan (University of Brawijaya, 2026)
This research aims to develop the digital pocketbook BISA.ID as a medium for learning Indonesian to enhance literacy among 2nd grade students at SD N 5 Kalierang. This study employs the Research and Development (R&D) method with the ADDIE development model (Analysis, Design, Development, & Implementation). Data were obtained through interviews, observations, and documentation, and were analyzed using the Miles & Huberman interactive analysis model. The research results show that the BISA.ID digital pocketbook is effective in supporting poetry learning and improving students literacy. This media is considered engaging, easy to use, and can bridge communication between teachers, students, and parents. These findings reinforce the importance of technological innovation in Indonesian language learning in elementary schools, particularly in strengthening skills in writing poetry.